2015
DOI: 10.1038/nphys3384
|View full text |Cite
|
Sign up to set email alerts
|

Accessing the fundamentals of magnetotransport in metals with terahertz probes

Abstract: Spin-dependent conduction in metals underlies all modern magnetic memory technologies, such as giant magnetoresistance (GMR). The charge current in ferromagnetic transition metals is carried by two non-mixing populations of sp-band Fermi-level electrons: one of majority-spin and one of minority-spin. These electrons experience spin-dependent momentum scattering with localized electrons, which originate from the spin-split d-band. The direct observation of magnetotransport under such fundamental conditions, how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
85
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(88 citation statements)
references
References 52 publications
2
85
0
1
Order By: Relevance
“…Moreover, this model predicts that the conduction is dominated by the majority-spin electrons, leading to a positive spin polarization of the current. This simple picture turns out to be quite accurate, as it has been very recently demonstrated using ultrafast terahertz spectroscopy [22]. However, as we shall show in this work, it severely fails to explain the transport properties in ferromagnetic atomic contacts.…”
Section: Introductionmentioning
confidence: 73%
“…Moreover, this model predicts that the conduction is dominated by the majority-spin electrons, leading to a positive spin polarization of the current. This simple picture turns out to be quite accurate, as it has been very recently demonstrated using ultrafast terahertz spectroscopy [22]. However, as we shall show in this work, it severely fails to explain the transport properties in ferromagnetic atomic contacts.…”
Section: Introductionmentioning
confidence: 73%
“…Thus τ s /τ p is also a constant, which indicates that the spin relaxation in Pt is governed by Elliott-Yafet mechanism [12]. We also applied a THz technique [56] to directly measure momentum relaxation time and resistivity of Pt with 30 nm thickness, which gives τ p =(5±3) fs and ρ Pt =16 µΩcm at 300 K. Assuming that τ p is proportional to 1/ρ Pt , τ p in Pt/MgO/CFB is thus around 2.7 fs. Therefore the spin flip probability of each scattering τ p /τ s is around 7×10 −4 for Pt at 300 K. Our ρ Ta is about 342 µΩcm at 300 K, much larger than those reported for the resistivity of α-phase and even β-phase Ta [57,58], which might be due to oxidation of Ta after the top structure is etched.…”
Section: Ishe 1ωmentioning
confidence: 99%
“…32,33 Indeed, it can be demonstrated that standard spinelectronic phenomena work at THz frequencies (Figure 4(a)). The GMR effect still operates at THz frequencies: Mott's two current model, with different relaxation channels on different spin channels, has been proven to be functional and different Drude relaxation times can be extracted for spin-up and spin-down electron transport 53 ( Figure 4(c)). The static GMR of 23% is comparable to the THz GMR of 25%.…”
Section: Novel Applications In the Thz Range A Thz Spintronicsmentioning
confidence: 99%